Performance of Palm Oil Fuel Ash Cement Based Aerated Concrete Subjected to Different Curing Regime Towards Carbonation - Khairunisa, Muthusamy; Mohd Warid, Hussin; Fadhadli, Zakaria (Pulau Pinang : Centre for Informayion Technology and Science Quantitative, 2006, 2006)
Since the early days, the never ending effort of researchers in improving and innovating products has lead to vast improvement in the existing human civilization now. In this century which is known as era of information technology, the availability of high-tech telecommunication network system has created an active knowledge sharing culture internationally. Thus, eventually motivating the researchers to be constantly innovating products to fulfill the growing demand of modern human society especially construction industry. The utilization of palm oil fuel ash (POFA) in concrete technology is one of the research areas that has been discovered in past century by Malaysian researchers and continually developed. Now in the 21st century, the Faculty of Civil Engineering of Universiti Teknologi Malaysia again revealed that this problematic waste which constantly produced abundantly by palm oil mill also has the prospect to be integrated as a partial cement replacement in aerated concrete. Therefore, the current objective of this investigation is to study the effect of different curing regime towards the carbonation resistance of palm oil fuel ash cement based aerated concrete. All specimens were cast in the prisms of (40x40x160mm) and then subjected to various curing regime that is natural weather curing, water curing, air curing and initial water curing followed by air curing. Then, carbonation test was conducted to the prisms aging 28 days in accordance to RILEM CPC 18 (1988). Based on the early studies, it was found that both specimen either consisting POFA or 100% cement subjected to natural weather curing exposed to higher carbonation as compared to any types of curing regime. Conclusively, POFA cement based aerated concrete is exposed to higher carbonation in all types of curing regime as compared to normal aerated concrete due its lower density.